Energy efficiency‐based device‐to‐device uplink resource allocation with multiple resource reusing. Issue 3 (1st February 2015) - Yang, Chengcheng; Xu, Xiaodong; Han, Jiang; Tao, Xiaofeng
Abstract : Device‐to‐device communication fulfils its potential in terms of high resource utilisation, thus it has been a hot topic in the recent long‐term evolution standardisation process. The general scenario with multiple resource pool multiplexing instead of the one‐time reusing is considered. Meanwhile, the optimisation target focuses on device energy efficiency under certain system throughput insurance rather than the traditional system throughput. A modified genetic algorithm‐based scheme is applied to address the facing non‐deterministic polynomial‐time hard problem with higher convergence and lower complexity.